Recent advances in breeding for autogamy in almond - Socias i Company R.; Felipe A.J. (XI GREMPA Seminar on Pistachios and Almonds, 2001)
Three new almond cultivars have been released from the almond breeding programme of the SIA-DGA of Zaragoza. They are distinguished by their autogamy, which allows their cultivation in solid plantings of a single cultivar. All of them produce high quality fruits with single kernels. They also show different blooming times and, consequently, they can be recommended for different growing regions. Their kernel characteristics will also offer different commercial possibilities.
11. GREMPA Seminar on Pistachios and Almonds, 1999/09/01-04, Sanliurfa (Turkey)